Predictors of parental leave support: Bad news for (big) dads and a policy for equality. (August 2018) - Gloor, Jamie L.; Li, Xinxin; Puhl, Rebecca M.
Parenthood increases gender inequality in paid (employment) and unpaid labor (e.g., caretaking). New parental leave plans aim to increase gender equality by reducing managerial discretion and offering gender-neutral benefits. However, coworkers may undermine these inclusive aims, particularly if they show variable support per employee characteristics. Thus, we examine why and how employee gender and obesity interactively predict coworkers' support for parental leave and test an intervention to increase equality. Three between-subjects experiments with working American adults ( N s = 133–252) indicate that obesity decreases coworkers' parental leave support for men, but increases coworkers' parental leave support for women; these effects are replicated and mediated by coworkers' caregiving ability expectations of the employees, inequalities that are reduced when parental leave is made the default. Discussion focuses on our results' implications for theory, practice, and for men and women's paid and unpaid labor, including recommendations for parental leave policy design and delivery to increase equality.